In the loop [videorecording (DVD)] - Iannucci, Armando, 1963-; Iannucci, Armando, 1963-; Capaldi, Peter; Hollander, Tom, 1967-; McKee, Gina, 1964-; Gandolfini, James; Addison, Chris, 1972- (IFC Films, 2010)
"The US President and UK Prime Minister fancy a war. But not everyone agrees that war is a good thing. The US General Miller doesn't think so and neither does the British Secretary of State for International Development, Simon Foster. But, after Simon accidentally backs military action on TV, he suddenly has a lot of friends in Washington, DC. If Simon can get in with the right DC people, if his entourage of one can sleep with the right intern, and if they can both stop the Prime Minister's chief spin-doctor Malcolm Tucker rigging the vote at the UN, they can halt the war."--Producers.